2007
DOI: 10.1152/ajpendo.00254.2006
|View full text |Cite
|
Sign up to set email alerts
|

Beyond lipids, pharmacological PPARα activation has important effects on amino acid metabolism as studied in the rat

Abstract: nists have been characterized largely in terms of their effects on lipids and glucose metabolism, whereas little has been reported about effects on amino acid metabolism. We studied responses to the PPAR␣ agonist WY 14,643 (30 mol⅐ kg Ϫ1 ⅐ day Ϫ1 for 4 wk) in rats fed a saturated fat diet. Plasma and urine were analyzed with proton NMR. Plasma amino acids were measured using HPLC, and hepatic gene expression was assessed with DNA arrays. The high-fat diet elevated plasma levels of insulin and triglycerides (TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 40 publications
9
55
1
Order By: Relevance
“…The amino acids linked to the urea cycle, which include aspartate, arginine, and citrulline, are increased in PPAR-a knockout mice compared with wild-type mice (59). In a model of dyslipidemia and insulin resistance, however, the PPAR-a agonist Wy14643 produces significant alterations in the plasma levels of both amino acids and nitrogen-containing metabolites, suggesting important effects on amino acid mobilization and catabolism (60).…”
Section: Metabolic Functions Of Ppar-amentioning
confidence: 99%
“…The amino acids linked to the urea cycle, which include aspartate, arginine, and citrulline, are increased in PPAR-a knockout mice compared with wild-type mice (59). In a model of dyslipidemia and insulin resistance, however, the PPAR-a agonist Wy14643 produces significant alterations in the plasma levels of both amino acids and nitrogen-containing metabolites, suggesting important effects on amino acid mobilization and catabolism (60).…”
Section: Metabolic Functions Of Ppar-amentioning
confidence: 99%
“…Furthermore, it has been suggested that treatment with synthetic ligands of PPARa is able to decrease the mRNA concentration of several enzymes responsible for amino acid catabolism and the urea cycle (20,21). Recently, it was also suggested that PPARa deficiency affects arginine metabolism, impairing NO synthesis (22).…”
Section: Introductionmentioning
confidence: 99%
“…9 Data in literature show that administration of PPARα agonist in mice results in increased levels and rate of turnover of glycine and serine in the plasma. 35 The physiological significance of changes in glycine and serine metabolism during protein restriction, other than as source of methyl groups, has not been determined. It has been postulated that restriction of dietary protein results in higher methylation demand and a high rate transmethylation and consequently high rate of synthesis of serine and glycine.…”
Section: Discussionmentioning
confidence: 99%